On Japanese literature of the Nara period (VIII century) - Mamatkulova Kholida Akhtamovna (Genius Journals, 2022)
This article describes the views on the Japanese literature of the Nara period (VIII century). As well as, within the framework of the article, there is talk about the unique role and characteristics of the literature of the Nara period in the flourishing of Japanese literature.
Keywords: Japanese; literature; Nara period; Heijyo